Um Sarau literário no seminário baiano : formação e desenvolvimento de leitores - Barreto, Maria Iraides da Silva (2011)
This work appears as an explanatory and literature research with a qualitative approach. This is a literary soiree held with students from the 3rd grade of High School "Colégio Seu Amado", located in the district of Pilar, city of Jaguarari in semi-arid of Bahia. This research tried to explain theoretically the practice of poetry reading as well as validate and authorize the experience scientifically. The thesis presented here come to a inverted path of those which thematize didactic proposals, because we start from a concrete practice in the search for theoretical foundations and methodological approaches. Our way as teachers of literature let us allowed that the students of this institution had attitudes of aversion and reject the readings of the canons of Brazilian Literature. Based on this principle, we were weaving a practice that included: readings of poems, novels, short stories, plays, the lyrics, reviews and abstracts of books and films, organization and display of virtual vernissages (paintings); performance of poetry recitals, reading, assembly and presentation of plays; session of films and documentaries, production of short videos. We realized from the research that the soirée raises questions based on the Bakhtinian notion of language as dialogic teaching of reading that emphasize interactions in the classroom, the specifics of writing fiction, the concept of literacy and literary literacy. It was particularly useful the concepts of Maingueneau about the pragmatic applied to literary texts and freinetiana pedagogy, which led the workshops or teaching workshops and working with projects that enable linkage with interactionism. To validate the data collection, we resorted to using a questionnaire with students and former students and testimonials to the team manager, with former students, parents and teachers, all recorded on video. We noticed that the literary soiree includes the precepts of LDB in force, and the DCNEM and OCEM not only on the aspects of citizenship formation, but because the activities highlight the dialogue between different fields of knowledge such as language, literature, history, informatics and visual and performing arts. This pedagogical nurture a collective meeting of the reader with the text, a process mediated by peers, by author, teacher, other texts, the relationship between the life of the author and his works, namely the "bio/graphy" (MAINGUENEAU, 2001). At the end of the work, it was established, in practice, the validity of Bakhtinian dialogism in teaching and learning of mother tongue as well as its consequences in artistic texts that use many different languages. The bias of literary literacy proved indispensable for the development and expansion of social literacy. All these concepts are identifiable in achieving this soiree that takes place almost a decade ago, and adding multiple languages, it is presented as a proposal to work productively with the fictional writing, contributing to improve teaching and learning Portuguese.